PERKAWINAN CAMPURAN DAN PERKAWINAN ANTAR-AGAMA DI INDONESIA - Rohman, Moh. Taufiqur (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2011)
Each aims to build a family wedding sakinah mawaddah warohmah. In an effort to create tujuan, Islam offers the compatibility between couples (kafa'ah), which matching in the social level or the same confidence. Islam is not too make a problem out of social level such as mixed marriages in Indonesia between the Indonesians and foreigners. Other difference is the case with religious marriage between Muslims and non-Muslim (especially of the Book), Islam clearly arranged. Although a statement of confidence can not be guaranteed the realization of the purpose of marriage, not all couples of like mind lives in harmonic, harmony, and peace, but sometimes couples of different religions living harmoniously, consistent and peaceful. This does not mean your wedding different confidence is better than on religion. If you look back wedding vulnerable religious conflict differently, both on the question of worship, religious and other children. Other than that in Indonesia and religious law forbids it.[Setiap perkawinan bertujuan untuk membina keluarga sakinah mawaddah dan rahmah. Dalam usaha mewujudkan tujuan tersebut, Islam menawarkan keserasian antara pasangan (kafa>’ah), yakni sepadan baik dalam strata sosial ataupun keyakinan yang sama. Islam tidak terlalu mempermasalahkan strata sosial seperti perkawinan campur yang ada di Indonesia antara warga Indonesia dan warga negara asing. Lain halnya dengan perkawinan beda agama antara Muslim dan non-Muslim (khususnya Ahli Kitab), Islam mengaturnya dengan jelas. Walau kenyataannya keyakinan tidak bisa menjadi jaminan terwujudnya tujuan perkawinan, tidak semua pasangan yang seiman kehidupannya harmonis, selaras, dan damai, malah kadang kehidupan pasangan yang berbeda agama lebih harmonis, selaras, dan damai. Ini bukan berarti pernikahan berbeda keyakinan lebih baik daripada seagama. Jika dilihat ke belakang, pernikahan beda agama rentan konflik, baik tentang soal ibadah, agama anak, dan lain-lain. Selain itu, di Indonesia Undang-undang dan agama melarangnya.]